EFFECT OF NON-SURGICAL THERAPY ON SALIVARY NITRIC OXIDE AND LIPID PEROXIDATION LEVELS IN TYPE II DIABETIC AND NON DIABETIC PATIENTS WITH PERIODONTAL DISEASE - Latha, Neena; Uppoor, Ashita; Nayak, Sangeeta Umesh; Naik, Dilip G (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Reactive oxygen species have been identified as potential factors causing periodontal tissue destruction. Elevated levels of these in patients with chronic periodontitis and diabetes may aggravate the oxidative stress burden thereby accelerating the tissue damage associated with diabetes. The present study aimed to assess the effect of diabetes and periodontal disease on the oxidative stress markers and the effect of non-surgical therapy on these markers. Methods: A total of 50 participants were divided into four groups based on the selection criteria. In addition to clinical parameters and biochemical parameters (salivary nitric oxide [NO] and malondialdehyde [MDA] levels) were assessed using spectrophotometric method at baseline and 3 months after non-surgical periodontal therapy. Result: There was a statistically significant difference in the clinical parameters as well as NO and MDA levels in patients with type 2 diabetes and chronic periodontitis than other three groups at baseline and at 3 months after non- surgical periodontal therapy. Conclusion: Diabetes mellitus and periodontitis have a compounding effect on the oxidative stress. Periodontal therapy is essential for diabetic patients as it can lower the levels of oxidative damage.